Analisis Manajemen Pemeliharaan Sarana Dan Prasarana Untuk Meningkatkan Kualitas Pendidikan - Syaiful Anam; Muhamad Nanang Rifa`i; Ajeng Nazah Fauziah (Gayaku Publisher, 2025)
Facilities and infrastructure management is all the process of managing and using tools and infrastructure that aims to find out how to manage and obstacles to maintaining facilities and infrastructure in schools. This research method uses qualitative methods with a qualitative descriptive approach and data collection tools in the form of observations, interviews, and documentation. The results showed that: 1) The student affairs department has planned a program of facilities and infrastructure to develop facilities in school activities. 2) The facilities and infrastructure are used in accordance with the learning needs of the teacher concerned and are regulated and supervised in an orderly manner. 3) Obstacles to lack of funds to equip facilities and infrastructure as well as acquisition and maintenance financing. Conclusion: the school can do a job easily and the effectiveness of the teaching and learning process runs smoothly, peacefully and comfortably. Because facilities and infrastructure are very important for both educators and students, especially in an effort to improve the quality of learning. The update is an evaluation material for every school resident to further improve the quality and management of facilities and infrastructure properly